Pengembangan Model Edukasi Telehealth terhadap Pencegahan Perilaku Seksual Pranikah pada Remaja: Literatur Review - Harini, Ririn; Susanti, Henny Dwi; Juwitasari, Juwitasari; Handayani, Tri Lestari (Universitas Tribhuwana Tunggadewi, 2023)
Pre-marital sexual behavior in adolescents can influence developmental tasks and increase risky behaviors such as unwanted pregnancies and sexually transmitted infections. Social media, gadget influence, and inappropriate peer selection play a role in these occurrences. Peer education models through counselling centers in schools are crucial in providing insights and experiences for better and healthier behavior. Telehealth models serve as an educational method that can reduce pre-marital sexual behavior by providing information on reproductive health and preventing pre-marital sexual behavior. The research method used was a comprehensive literature review. A total of 11 articles meeting inclusion criteria were found, utilizing educational media through m-health, WhatsApp groups, videos, and leaflets. Data gathered included insights into sexual diseases, positive attitudes towards change, adolescent knowledge and interests, education level, gender, self-efficacy, general health status, socioeconomic status, living conditions, healthcare facilities, and marital status. Clinical practice implications through peer education can enhance adolescent knowledge, thus potentially reducing premarital sexual relationships and unwanted pregnancies among adolescents. Based on the literature study, the telehealth education model can be further developed using other theoretical models to make its implementation more comprehensive.